Simulation of the behaviour of covid-19 with the stochastic SIRD model: case of Peru - Rubio, Obidio (2023)
In this work, we simulate the dynamics of COVID-19 pandemic using a deterministic SIRD model and its stochastic SIRD model version. The model is used under a closed population of 32 625 984 from the peruvian country, where the coefficient of the transmission rate, the recovery rate, the dead rate and the initial condition are given for the data taken from the initial days reported by the first disease people in Peru.